Memotret Masa Keemasan Peradaban dan Pendidikan Tiga Kerajaan Besar Islam - Fathorrahman . (STID Raudlatul Iman Sumenep, 2021)
The complete portrait of Islamic civilization in the world of education in the medieval period can be seen from the history of the three great dynasties, namely the Ottoman Turks, Safavids in Persia (Iran) and Moghuls in India. The three dynasties contributed significantly to the development of science in different portions. If at first in Ottoman Turkey only focused on military education and religious knowledge, then in the next leadership period general sciences were also used as study material in madrasas. It was different with the Safavid dynasty in Persia which tried to revive the passion of the century of scientific progress during the Abbasid period. During this Safavid period, quite a number of prominent scientists such as Baharuddin Syaerasi and others were born. Unlike the two previous dynasties, the achievement of scientific development in the Mughol Dynasty was represented by a historian during the Aurangzeb period, namely Abu Fadl with his work Aini Akhbari containing the history of the Mughal empire based on its leadership. Potret utuh peradaban Islam dalam dunia pendidikan pada periode pertengahan dapat dilihat dari sejarah tiga dinasti besar yakni Turki Usmani, Safawiyah di Persia (Iran) dan Mughal di India. Ketiga dinasti tersebut memberikan kontribusi yang sangat berarti bagi perkembangan ilmu pengetahuan dengan porsi yang berbeda. Jika pada mulanya di Turki Usmani hanya memfokuskan pendidikan pada ranah militer dan ilmu agama saja, maka pada periode kepemimpinan selanjutnya ilmu-ilmu umum juga dijadikan bahan pengkajian di madrasah-madrasah. Lain halnya dengan dinasti Safawiyah di Persia yang berusaha membangkitkan kembali gairah abad kemajuan ilmu pengetahuan pada masa Abbasiyah. Pada masa safawiyah ini cukup banyak melahirkan ilmuwan-ilmuwan terkemuka seperti Baharuddin Syaerasi dan lainnya. Berbeda dengan dua dinasti sebelumnya, pencapaian perkembangan ilmu pengetahuan di Dinasti Mughal diwakili oleh seorang sejarawan pada masa Aurangzeb yakni Abu Fadl dengan karyanya Aini Akhbari berisi tentang sejarah kerajaan Mughal berdasarkan pimpinannya.